2021
DOI: 10.3389/fpls.2021.670209
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow Risks From Transgenic Herbicide-Tolerant Crops to Their Wild Relatives Can Be Mitigated by Utilizing Alien Chromosomes

Abstract: Integration of a transgene into chromosomes of the C-genomes of oilseed rape (AACC, 2n = 38) may affect their gene flow to wild relatives, particularly Brassica juncea (AABB, 2n = 36). However, no empiric evidence exists in favor of the C-genome as a safer candidate for transformation. In the presence of herbicide selections, the first- to fourth-generation progenies of a B. juncea × glyphosate-tolerant oilseed rape cross [EPSPS gene insertion in the A-genome (Roundup Ready, event RT73)] showed more fitness th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Aside from that, GM crops and their transgenes spread via seed spillage during transportation and pollen-mediated gene transfers, resulting in feral populations [ 1 , 15 ]. If this occurs, weeds with GM traits may provide new and substantial weed control challenges [ 16 ]. The risk of crop genes transferring to weedy relatives is determined by their genetic and structural similarities as well as the strength of the transgenic selection in the weedy relative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from that, GM crops and their transgenes spread via seed spillage during transportation and pollen-mediated gene transfers, resulting in feral populations [ 1 , 15 ]. If this occurs, weeds with GM traits may provide new and substantial weed control challenges [ 16 ]. The risk of crop genes transferring to weedy relatives is determined by their genetic and structural similarities as well as the strength of the transgenic selection in the weedy relative.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of crop genes transferring to weedy relatives is determined by their genetic and structural similarities as well as the strength of the transgenic selection in the weedy relative. The transfer of transgenes through introgression also depends on the fitness of the first and successive generations of hybrids [ 16 , 17 , 18 ]. However, the level of hybridization and introgression among the Brassica species is highly varied.…”
Section: Introductionmentioning
confidence: 99%
“…As the typical relative of Brassica napus , wild Brassica juncea (AABB, 2n = 36), which was wildly distributed in the wastelands and farmlands of the Yangtze River Basin, Yellow River Basin and northwest China, represents a high gene homology with transgenic Brassica napus [ 7 ]. As a matter of fact, Brassica napus really hybridized with wild Brassica juncea to produce F1 under natural conditions [ 8 , 9 , 10 , 11 ], and the fitness of the progenies displayed increased fecundity and fitness progressively across the self-pollination of backcross generations, which indicated a potential ecological risk of transgene flow [ 12 , 13 , 14 ]. However, potential ecological risk depends on not only fitness of the hybrids but also genetic stability of the transgene, including its transmission and expression.…”
Section: Introductionsmentioning
confidence: 99%
“…However, there is no empirical evidence to describe this internal mechanism. Moreover, it was found that the survival rate of backcross progenies of HR transgenic Brassica napus ( PAT gene insertion in the C-genome) and wild Brassica juncea under herbicide selection was significantly lower than that of backcross progenies of resistant transgenic Brassica napus (EPSPS gene insertion in the A-genome) and wild Brassica juncea [ 14 ]. PAT is the type of N-acetyltransferase gene which has the detoxification effect of glufosinate.…”
Section: Introductionsmentioning
confidence: 99%
See 1 more Smart Citation